1982
DOI: 10.1029/ja087ia10p08174
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐particle interactions near ΩHe+ observed on board GEOS 1 and 2: 2. Generation of ion cyclotron waves and heating of He+ ions

Abstract: This work is a continuation of paper 1 (Young et al., 1981) and is devoted to the generation process of ion cyclotron waves (ICWs) and the acceleration of He+ ions up to suprathermal energies. Simultaneous measurements are used from the ion composition experiment (0 < E < 16 keV), the energetic particle experiment (24 < E < 3 300 keV), and the ULF wave experiment (0.2–10 Hz) on board the GEOS 1 and GEOS 2 spacecraft. General characteristics of the local time distribution of ICWs will be presented and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
188
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(200 citation statements)
references
References 31 publications
10
188
1
Order By: Relevance
“…The two-point, frequent measurements of the Van Allen Probes allow us to pinpoint local field and plasma conditions for EMIC waves in the inner magnetosphere. New insight into the excitation of EMIC waves from this report is as follows: [Kennel and Petschek, 1966;Roux et al, 1982]. The local wave occurrences are reconfirmed with the testing of linear theory, even though it has intrinsic limitations (see below).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The two-point, frequent measurements of the Van Allen Probes allow us to pinpoint local field and plasma conditions for EMIC waves in the inner magnetosphere. New insight into the excitation of EMIC waves from this report is as follows: [Kennel and Petschek, 1966;Roux et al, 1982]. The local wave occurrences are reconfirmed with the testing of linear theory, even though it has intrinsic limitations (see below).…”
Section: Discussionmentioning
confidence: 81%
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high f plasma, with plasma density above at least 100 cm −3 only exists just inside the plasmasphere or storm time plume, and while storm time ring current number density can increase up ∼10 cm −3 [Chen et al, 2010], corresponding to a maximum value of h hh ∼ 10% in such high f plasma. Ring current H + anisotropy rarely exceeds 2 [Roux et al, 1982]. Within the reasonable constraints h hh ≤ 10% and A hh ≤ 2, plasma conditions for EMIC waves in resonance with MeV electrons are required to have at least f > ∼25 and A hh > 1.…”
Section: Electron Minimum Resonant Energiesmentioning
confidence: 99%
“…This assumption can seriously break down near W He +, where the He + resonant energy is comparable to or less than the He + thermal energy. Earlier observations [Young et al, 1981;Roux et al, 1982] have shown that He + ions can be heated in the direction perpendicular to the magnetic field line up to suprathermal energies (∼a few 100 eV) when EMIC waves were detected, suggesting a net energy transfer from EMIC waves to He + ions. This is consistent with severe cyclotron damping by He + near W He+ found in ray tracing study by Chen et al [2009], showing suppression of the instability just below W He+ (>3.75W O+ ).…”
Section: Introductionmentioning
confidence: 99%